Insulin resistance dealt with homoeopathy - Tripathy, Tridibesh; Das, Shankar; Dwivedi, Rakesh; Nayak, C.; Singh, D. P.; Tripathy, B.; Sahu, D. R.; Gautam, Mohini; Prusty, Umakant; Pradhan, P. B.; Pattnaik, J. K.; Pandey, S. N.; et al. (International Journal of Advances in Medicine, 2024)
One of the intricacies of diabetes is to understand the phenomenon of insulin resistance (IR). The phenomenon of IR applies to all types of diabetes. IR is a condition where the body’s cells stop responding to the glucose control hormone. In the current article, the lead author focuses on the IR related intricacies of diabetes and the role of homoeopathy in all the 4 types of diabetes. The first three types ate type 1, type 2 and type 3 the 4th type is maturity onset of diabetes in the young (MODY). The IR phenomenon cuts across among all sections of population including the working group and that’s why the discussion of IR is related to the growing economy as it puts burden on the economy. The article discusses the epidemiology, patho-physiology, prevention, control and treatment of IR especially at the global and national level. Thereafter, it discusses the integration of homoeopathy in to the IR domain. The properties of homoeopathy regarding the essential medicine (EM) in the national list of EM (NLEM) and the national list of essential AYUSH medicines (NLEAM) are also dealt upon. A suggested treatment protocol based on homoeopathic therapeutics is given at the end of the article after focusing on the burden of IR at national level through data from large scale surveys. In that section, the benefits that are to be accrued as a result of homoeopathic integration is also touched upon.